Uncovering the elements, viewer’s perception and factors of violent content in Netflix ‘You’ drama series - Mohamad Razali, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This qualitative study focuses on the elements, viewer's perception and factors of violent content in the Netflix 'You' drama series. Three research objectives were addressed: (1) To analyse the elements that influence the viewers' perception to watch Netflix 'You' drama series, (2) To identify the viewers' perception of reality in the violent content portrayed in the Netflix 'You' drama series, and (3) To identify the contributed factors generating the viewers' perception of reality on the violent content portrayed in the Netflix 'You' drama series. The Cultivation Theory guided this study where meaningful findings were obtained through in-depth interviews with six (6) informants who subscribed to Netflix, watched 'You' drama series for season one and season two, which lived in the Klang Valley. Data analysis were conducted with data gathering and using the NVivo to analyse the coding. The thematic analysis was used to analyse the data. Overall, the findings revealed significant themes in every research questions. For RQ1, the elements that influence the viewers' perception of watching 'You' drama series on Netflix were genre selection, binge-watching, and attraction to violent content. For RQ 2, the viewers' perception of reality on the violent content portrayed in the Netflix 'You' drama series has been revealed through the act of murder and torture, brutal actions, anxiety, fear and cautiousness. The RQ3 has revealed the accepting and dismissing violence, personal, and other experiences were the contributed factors generating the viewers' perception of reality on the violent content portrayed in the Netflix 'You' drama series.